The Implementation of Akhlak-Based Local Content Curriculum in Bangka Tengah Regency - Suparta Suparta (Postgraduate Program, State Institute on Islamic Studies Purwokerto, 2020)
Akhlak or moral education, which should be applied in the family, at school, and in the societies, is considered as the key success of education. However, most children are equipped with only cognitive religious knowledge without any formation of faith foundation. As a result, most children are good at knowledge and intelligence but poor behaviour. To avoid such condition, it is necessary to consider Islamic teachings as not only the objects of study and memorization, but as the values that should also be implemented. This ideal condition is intended to minimize the tendency that many adolescence orient to the material welfare and hedonism, which have made them have poor morals and spirituality. As a result, they do not have an Islamic personality, but an instant personality influenced by destructive content they watch from various media. To avoid a further destruction and to improve such condition, there should be a moral-based local content curriculum.